Character Education Model Based on Pancasila and National Resilience in Elementary Schools - Amiroh, Yara Ummi (International Journal of Students Education, 2024)
Education character based on Pancasila And resilience national is investment term long for build a more nation good. With implementing educational models the right character, it is expected generation young Indonesia can grow become a person with good morals noble, insightful wide, and own spirit high nationality. The urgency of character education in the era of globalization is at the level of urgent and important needs, because the rapid progress of science and technology must be accompanied by character strengthening for its users. Character education is the answer to concerns about the negative effects of the era of openness of information which results in the decline of the noble values of the nation’s culture which leads this nation to a moral crisis. The purpose of this study is to determine how the model of character education based on Pancasila and national resilience in elementary school children using the method study qualitative with study approach literature. Results research show that the PPKN teacher play a role important to plant values of the “ Education Model” character based on Pancasila and resilience national in schools the basis" can be found in the discussion of Pancasila-based education so that it can be concluded through the meaning and model of education.